Ballast water management - current trends and economic impact of recently adopted regulations on the seafreight transportation market - Pavlíčková, Veronika; Kolář, Petr; Rožek, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
This master thesis deals with the very current topic of ballast water management, a very specific field in the maritime shipping industry. The aim of the thesis is to introduce the subject clearly and to sum up the main issues which restrain a smooth implementation of new regulations that emerged from a recently adopted international treaty. This treaty, the so-called Ballast Water Management Convention, will possibly have immediate impact on the seafreight market rates and thus on the entire international trade. So purpose of this thesis is to estimate what the result might be like.
Vedoucí práce: Petr Kolář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses